The Earth Science Box Modeling Toolkit (ESBMTK 0.14.0.11): a Python library for research and teaching - U. G. Wortmann; T. Tsan; M. Niazi; I. A. Ma; R. Navasardyan; M.-R. Marun; B. S. Chede; J. Zhong; M. Wolfe (Geoscientific Model Development)
The Earth Science Box Modeling Toolkit (ESBMTK) is a Python library that streamlines the creation and analysis of box models in earth sciences. With its modular, object-oriented design, ESBMTK simplifies the study of systems such as the long-term carbon cycle or the impact of atmospheric CO2 variations on ocean chemistry. By standardizing and clarifying how models are defined, the library enhances code readability and serves as a self-documenting tool, making it approachable for undergraduate students and efficient for researchers. ESBMTK automatically translates user-defined models into equations which are solved using established numerical libraries. It also includes built-in functionality for common tasks such as ocean–atmosphere gas exchange, marine carbonate chemistry, isotope effects, and perturbation scenarios. The library's core interface is stable, supported by comprehensive documentation, and available as open-source software through the pip and conda package management systems.